Technological sophistication made in China? New insights from Germany's evaluation of COVID-19 antigen rapid tests - Silas Dreier; Wan-hsin Liu (Kiel Centre for Globalization (KCG), 2023)
By analyzing a unique dataset from Germany's evaluation of COVID-19 antigen rapid tests, we show that Chinese firms can excel under today's global competition and produce tests at quality levels higher than China's income level would suggest. We find these achievements are positively associated with China's rising innovation capability and robust industrial base. Further strengthening China's innovation and industrial base to support Chinese firms' future accomplishments is what the Chinese government clearly aims for. This would intensify the challenges facing Western economies that strive for technological sovereignty and eagerly seek to de-risk their economic relations with China.
Keywords: F10; O10; O30; 330; China; product quality; technological sophistication; trade; COVID-19